Pendampingan UMKM Dodol Melalui Branding Digital di Desa Lahang Baru Kecamatan Gaung - Kurniawan, Danny; Nisa, Khaerun; Nurkhapiza, Salma; Ardiansyah Putra, David; Hakri, M. Akmal; Prorina, Riska; Indah Putri, Marisa; Nurkafi, Febriyana; Pertiwi, Kamia; Adi Putra, Bambang Sasmita (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the economy, particularly in preserving the sustainability of regional traditional products. However, limited branding and digital marketing often become obstacles in business development. This study aims to analyze the assistance provided to “Dodol Ibu Lina,” a traditional dodol producer from Lahang Baru Village, Gaung District, Indragiri Hilir Regency, through strategies including logo and brand identity creation, packaging development, business legalization, as well as the creation and optimization of online sales accounts on Shopee and TikTok Shop. The research method used is a case study approach with field observations, interviews, and documentation. The results show that prior to the assistance, Dodol Ibu Lina was marketed conventionally through word-of-mouth promotion, using plain plastic packaging without labels, having no logo, not being officially registered as an MSME, and not utilizing online marketing. After the assistance, the business successfully obtained a clear brand identity, cardboard packaging with attractive designs and product information, a registered location on Google Maps, official business permits, and active online sales accounts with integrated digital promotion strategies. These changes expanded the market reach from only.